Hermeneutik und Kritik - Schleiermacher, Friedrich 1768-1834; Frank, Manfred -1945 (Frankfurt am Main Suhrkamp, 1977)
Schleiermacher wanted to shift hermeneutics away from specific methods of interpretation (e.g. methods for interpreting biblical or classical texts) and toward a focus on how people understand texts in general. He was interested in interpreting Scripture, but he thought one could do so properly only after establishing a system of interpretation that was applicable to all texts. This process was not a systematic or strictly philological approach, but what he called "the art of understanding." Schleiermacher viewed a text as a vehicle that an author used to communicate thoughts that he had had before creating the text. These thoughts were what caused the author to produce the text; at the moment of text creation, these "inner thoughts" become "outer expression" in language. In order to interpret a text, then, the interpreter must consider both the inner thoughts of the author and the language that s/he used in writing the text. This approach to interpreting texts involves both "grammatical interpretation" and "psychological (or technical) interpretation." The former deals with the language of the text; the latter with the thoughts and aims of the author.
Friedrich Daniel Ernst Schleiermacher (1768-1834) was a German Reformed theologian, philosopher, and biblical scholar known for his attempt to reconcile the criticisms of the Enlightenment with traditional Protestant Christianity. He also became influential in the evolution of higher criticism, and his work forms part of the foundation of the modern field of hermeneutics. Because of his profound effect on subsequent Christian thought, he is often called the "Father of Modern Liberal Theology" and is considered an early leader in liberal Christianity.
Includes bibliographical references.
Keywords: 18th Century (1701-1800); 19th Century (1801-1900); Philosophy; Hermeneutics; Crescendo; Religion; Germany